Health- and Non–Health-Related Corporate Social Responsibility Statements in Top Selling Restaurant Chains in the U.S. Between 2012 and 2018: A Content Analysis - Megan P. Mueller, PhD; Alyssa Leib, MS; Deborah C. Glik, PhD; Sara N. Bleich, PhD; Jason Wang, PhD; Catherine M. Crespi, PhD; May C. Wang, DrPH (AJPM Focus)
Introduction: The aim of this study was to understand the prevalence and content of corporate social responsibility statements in the top-selling chain restaurants between 2012 and 2018 to inform the ways restaurants can impact population health. Methods: The study used a web scraping technique to abstract relevant text information (n=6,369 text sections that contained possible corporate social responsibility statements or thematically coded portions of the text section) from the archived web pages of the 96 top-selling chain restaurants. Content analysis was used to identify key themes in corporate social responsibility statements across restaurants and over time. All data were abstracted, and analyses were completed between November 2019 and November 2023. Results: The majority of restaurants (68.8%) included a corporate social responsibility statement on their web pages between 2012 and 2018, and approximately half of the restaurants featured a health-related corporate social responsibility statement (51.0%). There were increases in corporate social responsibility statements by chain restaurants over the study period from 186 corporate social responsibility statements in 2012 to 1,218 corporate social responsibility statements in 2018, with most statements focused on philanthropy (37.1% of coded statements), community activities that were not health related (18.4% of coded statements), and sustainability initiatives (18.3% of coded statements). Only one quarter (24.4%) of these corporate social responsibility statements were health related, and many were vague in nature (only 28% of the eligible statements could be coded by theme). Conclusions: There is a need for more actionable health-focused initiatives in the corporate social responsibility statements for chain restaurants. Public health initiatives that engage with the restaurant industry should work to promote corporate social responsibility statements that are in line with other collective positions around improving health and reducing diet-related disease.